2009
DOI: 10.1007/s12207-009-9045-4
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder: Assessing Response Style and Malingering

Abstract: Posttraumatic stress disorder (PTSD) may form the basis for disability or worker's compensation claims or a personal injury lawsuit. While now achieving widespread acceptance among treating professionals and the public, PTSD is the subject of several controversies and the possibility of faking in a compensation context. There appears to be a dramatic split among mental health professionals who write primarily from a treatment or plaintiff perspective and those who take a more skeptical approach. This article r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 179 publications
(230 reference statements)
1
23
0
1
Order By: Relevance
“…The utility of its RBS scale (Response Bias Scale; Gervais et al 2007 ) is unknown. Howe agreed with Rubenzer ( 2009 ) that "no fi rm recommendations can be made regarding cutoff scores for the validity scales" of the MMPI-2, although they should be set for high specifi city. As for the PAI validity indicators, many claimants who are faking escape detection.…”
Section: Rosen and Grunert (2012)mentioning
confidence: 97%
See 1 more Smart Citation
“…The utility of its RBS scale (Response Bias Scale; Gervais et al 2007 ) is unknown. Howe agreed with Rubenzer ( 2009 ) that "no fi rm recommendations can be made regarding cutoff scores for the validity scales" of the MMPI-2, although they should be set for high specifi city. As for the PAI validity indicators, many claimants who are faking escape detection.…”
Section: Rosen and Grunert (2012)mentioning
confidence: 97%
“…Cognitive defi cits that precede the trauma constitute risk factors (Parslow and Jorm 2007 ). Multiple comorbidities complicate assessment and these might be due to intentional symptom over-endorsement, among other factors (Rubenzer 2009 ).…”
Section: Prevalencementioning
confidence: 99%
“…The former countered that a study by Greiffenstein et al (2007) had found that only 1.2% of respondents without a clear incentive to exaggerate exceeded this cutoff (false positives, N=1,052). According to Kane and Dvoskin, in his literature review, Rubenzer (2009) found a low false positive rate for the validity of the FBS in non-litigating cases. However, Kane and Dvoskin commented that "the false positive rate remains a concern."…”
Section: Testing and Diagnosis Of Psychological/psychiatric Injurymentioning
confidence: 99%
“…This illustrates that there is not one compendium that would satisfy all professionals, and in any one particular case, each practitioner is responsible for the choice of the tests used and the justifications for their selection. For the evaluation of PTSD, Rubenzer (2009) emphasized the MMPI-2 and the SIRS, as well as other tests. Rubenzer added that the newer MMPI-2 respondent validity check scales, such as the Response Bias Scale (RBS; Gervais et al 2007Gervais et al , 2008Gervais et al , 2009aWygant et al 2010) and the Henry Heilbronner Index (HHI; Henry et al 2006), hold great promise, as does the MMPI-2 RF (BenPorath and Tellegen 2008) and its revised respondent validity scales (Gervais et al 2009a, b).…”
Section: Testing and Diagnosis Of Psychological/psychiatric Injurymentioning
confidence: 99%
See 1 more Smart Citation